Numerical Simulation of Gas-Solid Two-Phase Flow in Horizontal Pipe : Interaction between Two Phases and Change of Energy Due to Collision of Particle - Peng, Xinjian; Tomita, Yuji; Tashiro, Hiroyuki (Nihon Kikai Gakkai rombunshuu. B hen, 1995)
A numerical simulation of gas-solid two-phase flow is carried out for mixed-size coarse particles and for uniform ones in a horizontal pipe of 40 mm inside diameter for mean air velocities of 12 and 16 m/s and solid loading ratio less than 1.14. Interaction between gas and particles is considered in the mean flow level of gas. The gas flow profile is modified by particles when the loading ratio is large, and the modification is significant in the acceleration region of particles. The main source of particle rotation is collision with the pipe wall and the particle-particle collision decelerates the rotation. The particles lose kinematic energy mostly by collision with the wall.